(3QSGdI GdWjQs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3gd dCMOi CNhGfi ai Cf jgH di SeYg bOQ eG Gdbi Edjg WQakG ef CTLGfi YSGg jMed Yfi HGdTQcI HYV CYHGFgG s
(3BNQgG (B:s
(3hHGddg GdCSJYGfI hYf GdfGS GdHQGI hef GYJbO ZjQ gPG NSQ s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGefIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B877s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs